Complete oxidation of linear alkylbenzene sulfonate by bacterial communities selected from coastal seawater. - Sigoillot, J C (1992)
Anionic surfactants, especially alkylbenzene sulfonates, are discharged into marine areas in great quantities. Because of their poor biodegradability, linear alkylbenzene sulfonates accumulate in seawater and sediments. Bacterial communities that can degrade surfactants were selected from coastal seawater contaminated by urban sewage. All the isolated strains consisted of gram-negative, strictly aerobic rods or helical bacteria. Some of these, though isolated from coastal seawater, did not need sodium for growth and appeared to be related to the genera Alcaligenes and Pseudomonas. Complete surfactant biodegradation was achieved by three important steps: terminal oxidation of the alkyl chain, desulfonation, and aromatic-ring cleavage. Only a few strains were able to carry out the first two steps. The aromatic ring was then cleaved by other strains that possess very specific enzymatic activities. Finally, a number of strains grew on short acids that were end-of-metabolism products of the others.